Designing and evaluating a culturally grounded digital parenting initiative in Malaysia - Mohamed, Shafizan; Janon, Nazariah Shar'ie; Yusoh, Mohd Helmi; Salleh, Norsaremah; Mohd Nasir, Nur Shakira; Wan Mohd Ghazali, Wan Norshira (IIUM Press, 2025)
The widespread adoption of digital technologies in Malaysia, with internet penetration reaching 97.4% in 2023, has profoundly redefined childhood experiences. While digital parenting principles are globally recognised, their application in Malaysia is shaped by socio-cultural diversity, religious beliefs, and economic inequalities, and existing parenting resources often lack sustained, culturally competent guidance. This study employed a mixed-methods design, combining a nationwide market validation survey of Malaysian parents (n = 240) with focus group discussions involving participants from diverse backgrounds, to examine challenges, preferences, and expectations in digital parenting. Findings reveal that parents struggle with screen time regulation, online risk management, and awareness of harmful content, issues further compounded by disparities in digital literacy. Parents expressed strong demand for short-form, visually engaging, and interactive content, alongside features such as expert-led Q&A, age-specific content filtering, and peer-sharing narratives, while also emphasising the importance of moral and faith-based guidance embedded in Islamic and cultural values. Evaluation of the Platform Keibubapaan Digital (Platform KID) prototype highlighted the need for greater interactivity, community engagement, and personalisation. By synthesising global best practices with local cultural contexts, the study informs the development of Platform KID as a model for empowering Malaysian parents with the skills, confidence, and ethical frameworks to raise digitally resilient children, with implications that extend beyond Malaysia to other Muslim-majority and multicultural societies